1986
DOI: 10.1007/bf00034941
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the ribosomal RNA genes among individuals of Vicia faba

Abstract: Length heterogeneity in the ribosomal repeat of Vicia faba is due to the presence of variable numbers of a 325 bp subrepetitive element within the nontranscribed spacer region. The distribution of size classes among 88 individuals within a population was investigated by blot-hybridization. We find that individual plants can exhibit more than 20 size classes and that hybridization patterns are highly diverse from individual to individual, more so than for any species so far investigated. In contrast, no such di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…In recent years, Hoechst dye 33528, which binds preferentially to A-T3 rich regions of DNA, has become increasingly useful in resolving cp-and mtDNA from nDNA in algae (1,14,19) and terrestrial plants (25). Organelle DNA species frequently migrate as low density satellite bands above the main nuclear DNA band in the Hoechst dye-CsCl gradients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Hoechst dye 33528, which binds preferentially to A-T3 rich regions of DNA, has become increasingly useful in resolving cp-and mtDNA from nDNA in algae (1,14,19) and terrestrial plants (25). Organelle DNA species frequently migrate as low density satellite bands above the main nuclear DNA band in the Hoechst dye-CsCl gradients.…”
mentioning
confidence: 99%
“…These Hoechst dye-CsCl gradients have also been exploited in the separation of terrestrial plant nuclear ribosomal DNA from total cellular DNA. Ribosomal DNA frequently appears as a high density satellite band below the nDNA in these gradients (25).…”
mentioning
confidence: 99%
“…For example, Rogers & Bendich (1987) reported a 12-fold variation within individuals, but almost a 95-fold difference among individuals within a population of Vicia faba. In maize, Buescher et al, (1984), reported a 4.6-fold difference among individuals; while Zhang et al, (1990) found a 6.4-fold difference among individuals The dwarf nature of these populations has been described as an apparent adaptation to higher fire frequencies relative to the other parts of the Pine Barrens, as well as to the distribution range of pitch pine (Ledig & Fryer, 1973;Good & Good, 1975;Givnish, 1981).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, no conclusion can be drawn about, (a) intra-individual variation for copy numbers, (b) absolute maximum and minimum number of copies among individuals in any given population, and (c) if there are dines (smooth vs. stepped; Endler, 1977) for copy numbers between populations in relation to environmental gradients. Variation for rRNA genes within individuals has been reported in organisms such as Drosophila (Tartoff, 1975), Neurospora (Russell & Rodland, 1986) and Vicia (Rogers & Bendich, 1987). Pitch pine is known to sprout by means of epicormic buds (buds under bark) following fire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation